Role of macrophage migration inhibitory factor (MIF) in pollen-induced allergic conjunctivitis and pollen dermatitis in mice. - Yuka Nagata (PLoS ONE, 2015)
Pollen is a clinically important airborne allergen and one of the major causes of allergic conjunctivitis. A subpopulation of patients with atopic dermatitis (AD) are also known to have exacerbated skin eruptions on the face, especially around the eyelids, after contact with pollen. This pollen-induced skin reaction is now known as pollen dermatitis. Macrophage migration inhibitory factor (MIF) is a pluripotent cytokine that plays an essential role in allergic inflammation. Recent findings suggest that MIF is involved in several allergic disorders, including AD. In this study, MIF knockout (KO), MIF transgenic (Tg) and WT littermate mice were immunized with ragweed (RW) pollen or Japanese cedar (JC) pollen and challenged via eye drops. We observed that the numbers of conjunctiva- and eyelid-infiltrating eosinophils were significantly increased in RW and JC pollen-sensitized MIF Tg compared with WT mice or MIF KO mice. The mRNA expression levels of eotaxin, interleukin (IL)-5 and IL-13 were increased in pollen-sensitized eyelid skin sites of MIF Tg mice. An in vitro analysis revealed that high eotaxin expression was induced in dermal fibroblasts by MIF combined with stimulation of IL-4 or IL-13. This eotaxin expression was inhibited by the treatment with CD74 siRNA in fibroblasts. These findings indicate that MIF can induce eosinophil accumulation in the conjunctiva and eyelid dermis exposed to pollen. Therefore, targeted inhibition of MIF might result as a new option to control pollen-induced allergic conjunctivitis and pollen dermatitis.